(untitled) - Prentice, William E. (Boston, MA., 2005)
Athletic Training is a much condensed version of the classic text Arnheim’s Principles of Athletic Training. Providing only those chapters that would effectively introduce the athletic training student to professional practice, it is designed for instructors who do not wish to cover the applications of athletic training in their first class. For those who are following the new curriculum requirements, the text introduces the athletic training student to the dynamic trends of the profession, while still providing a valuable resource for those eventually seeking professional certification.
Keywords: Sports medicine.,Sports injuries,Physical education and training; Prevention